Role of fine needle aspiration cytology (FNAC) in diagnosing Pancreatic lesions in a tertiary care institution - Jain, Sonia; Selhi, Pavneet Kaur; Kaur, Harpreet; Gupta, Ajay; Prakash, Siddharth (British Journal of Healthcare and Medical Research, 2021)
OBJECTIVE- FNAC is an accurate and rapid technique for diagnosing pancreatic masses. Pancreatic carcinoma represents the seventh leading cause of cancer death in the world, responsible for more than 300,000 deaths per year.[1] Worldwide, both the incidence and death rates of pancreatic cancer are increasing. The aim of this study was early diagnosis of these lesions and to evaluate its burden and study the global, regional, and national patterns. These would further aid in policy making , better resource allocation for controlling pancreatic cancer risk factors and formulating more effective treatments.[2] METHODS- This was a retrospective observational study performed at a tertiary care hospital over a period of one and a half year. A total of 86 patients with pancreatic lesions were subjected to image guided FNA . 35 of these patients underwent diagnostic histopathology in addition to FNA. RESULTS- The 86 cases analyzed were in the age group of 61-70 years with mean age distribution of 57.34 years. Male predominance was seen with M:F ratio of 2.18:1. Head was the most common area to be aspirated followed by tail and least number of lesions were in body of pancreas. Maximum cases were found to be malignant (55) in etiology. Only 2 were non diagnostic because one of them had insufficient cellularity and other had necrosis mainly on histopathology. Adenocarcinoma was the most common malignancy found followed by one case each of lymphoma and solid pseudo papillary neoplasm of pancreas. Histo pathological correlation was obtained in 91.42% cases proving that FNA is a very useful tool in early diagnosing pancreatic lesions.